2022
DOI: 10.3389/fcvm.2022.801511
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Conservative Treatment of Post-infarction Left Ventricular Pseudoaneurysm

Abstract: BackgroundPost-infarction left ventricular (LV) pseudoaneurysm is a rare mechanical complication of myocardial infarction that carries a substantial risk of sudden rupture. The purpose of this study was to compare the surgical results of post-infarction LV pseudoaneurysm with those of conservative treatment.MethodsFrom 2016 to 2021, 22 patients were hospitalized for LV pseudoaneurysm, including 17 cases (77.3%) caused by myocardial infarction. Of the 17 patients, 10 (58.8%) underwent surgical repair, while sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Zhong et al . 9 reviewed 17 cases of post–myocardial infarction LV pseudoaneurysms, 10 of which were managed surgically and the remainder medically. All patients who were treated surgically survived, with a mean follow-up duration of 18.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al . 9 reviewed 17 cases of post–myocardial infarction LV pseudoaneurysms, 10 of which were managed surgically and the remainder medically. All patients who were treated surgically survived, with a mean follow-up duration of 18.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival was higher among the surgical group compared with the medically managed group (100% vs 57%, P = .02). 9 Medical therapy alone is associated with risk, but long-term survival has been described. In our patient, the surgical risk was believed to be prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…In left ventricular (LV) ruptures with pseudoaneurysm, surgical repair is superior to conservative management [22 , 23] . Additionally, the risk of stroke from an untreated LV pseudoaneurysm poses a significant risk from the accumulating thrombus [24] .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous literature ( Table 1 ), most patients accepted surgical therapy. The outcomes were diverse in different clinical centers, operation associated mortality ranged from 0 to 35.7% ( 1 3 , 5 – 11 ), mortality during follow-up ranged from 0 to 31% ( 1 6 , 8 11 ), and patients with acute pseudoaneurysm or high surgical risks had higher mortality ( 3 ). The mortality of conservative therapy was also discussed in some studies with a small sample size, which appeared to be higher than surgical therapy ( 1 , 4 , 5 , 7 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes were diverse in different clinical centers, operation associated mortality ranged from 0 to 35.7% ( 1 3 , 5 – 11 ), mortality during follow-up ranged from 0 to 31% ( 1 6 , 8 11 ), and patients with acute pseudoaneurysm or high surgical risks had higher mortality ( 3 ). The mortality of conservative therapy was also discussed in some studies with a small sample size, which appeared to be higher than surgical therapy ( 1 , 4 , 5 , 7 , 11 ). Meanwhile, some retrospective studies reported patients with chronic small (< 3 cm in size) LV pseudoaneurysm or patients with high surgical risks could be managed conservatively ( 12 ).…”
Section: Discussionmentioning
confidence: 99%